Manajemen Konflik Hak Penerbitan Berita Google dan Australia - Haris Saefulloh; Ludiro Madu (Global Political Studies Journal, 2022)
Google and Australia undertake news publishing rights conflict management in 2021. In that conflict Australia wants Google to pay media companies for any news they publish online. The peak of the conflict occurred when Google did not agree and had threatened to leave. The theory used in this research is conflict management theory. The theory states that there are five types of conflict management that can be used depending on the priorities of the conflict actors. This type of research is a descriptive qualitative research. Data was collected using the document method which was then analyzed using the Miles and Huberman model. The result of this research is that Google and Australia have reached a compromise after one year of negotiations in the conflict of news publishing rights. This compromise is contained in an amendment to the News Media Bargaining Code which was originally used as a tool for the Australian Government to achieve its goals. Keywords : Australia, Digital Platform, Google, News Media Bargaining Code